Differences in Expression of Selected Interleukins in HIV-Infected Subjects Undergoing Antiretroviral Therapy - Szymańska, Beata; Jurkowska, Karolina; Knysz, Brygida; Piwowar, Agnieszka (Viruses, 2022)
The use of combined antiretroviral therapy (cART) inhibits the replication of the Human Immunodeficiency Virus (HIV) and thus may affect the functioning of the immune system, e.g., induce changes in the expression of certain cytokines. The aim was to examine the effect of cART on the expression of selected cytokines: interleukin -4, -7 and -15 in HIV-infected subjects. The test material was the plasma of HIV-infected men and healthy men (C, control group). The levels of interleukin were measured by immunoenzymatic method before cART and one year after treatment in relation to the C group. HIV-infected men were analyzed in subgroups depending on the HIV-RNA viral load, CD4+ and CD8+T-cell counts, and the type of therapeutic regimen. A significantly higher level of IL-4 was demonstrated in HIV-infected men before cART compared to those after treatment and in the control group. The use of cART resulted in a significant decrease in the level of IL-7 in HIV-infected men; however, high levels of IL-7 were associated with a low number of CD4+ T cells and CD8+ T cells. An increase in the level of IL-15 in HIV-infected men was noted after the use of cART. There was no difference in the expression of interleukins depending on the treatment regimen used. The study showed the effect of cART on the expression of interleukins, especially IL-4 and IL-7. Further research in this direction seems promising, confirming the role of these interleukins in the course of the disease.